2012
DOI: 10.1002/app.37517
|View full text |Cite
|
Sign up to set email alerts
|

Permeation resistance of poly(ether ether ketone) to hydrogen, nitrogen, and oxygen gases

Abstract: We studied the gas permeation properties of poly(ether ether ketone) (PEEK) and compared it with two other polymers commonly used in the construction of semiconductor microenvironments, polycarbonate (PC), and poly(ether imide) (PEI). The PEEK specimens consisted of extruded films as well as compression-and injection-molded specimens. The compression-molded specimens were prepared to achieve the highest crystallinity. Injection-molded disks, representing products, were milled to a prescribed thickness. Permeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…PEEK is highly resistance to permeation and diffusion of gases due to its morphology and degree of crystallinity. The permeability, diffusion, and solubility coefficients on PEEK films for oxygen have been found to be independent of applied upstream pressure and thickness . It has been also reported that diffusion coefficient was reduced with increasing crosslinking density .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…PEEK is highly resistance to permeation and diffusion of gases due to its morphology and degree of crystallinity. The permeability, diffusion, and solubility coefficients on PEEK films for oxygen have been found to be independent of applied upstream pressure and thickness . It has been also reported that diffusion coefficient was reduced with increasing crosslinking density .…”
Section: Resultsmentioning
confidence: 82%
“…The permeability, diffusion, and solubility coefficients on PEEK films for oxygen have been found to be independent of applied upstream pressure and thickness. 30 It has been also reported that diffusion coefficient was reduced with increasing crosslinking density. 13 Based on these the following conclusion could be made: At high dose rates, the atmospheric oxygen is consumed on the surface before it diffuses to the centre of the polymer and degradation will occur heterogeneously and not homogeneously.…”
Section: Resultsmentioning
confidence: 93%
“…The cost of sending materials to space has been estimated to be almost $11,000 kg −1 –$20,000 kg −1 (€9,800 kg −1 –€17,800 kg −1 approximately) with the cost significantly affected by launch type and final orbital position of the payload, and so reducing the weight of inherent systems is a main priority for future launch designs . A number of studies have already focused on the barrier properties of polymers in similar applications with PTFE, PFA, and PEEK exhibiting good barrier properties to gas permeation . Polymer liner studies have also been applied directly to COPV structures with a myriad of polymer materials being tested to determine their overall permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively large permeability observed for all PSU-QA samples, in comparison with SPEEK membranes showed previously, can be related to the higher permeation values of PSU in comparison with PEEK [23][24][25][26] , although in SPEEK the Donnan effect is absent.…”
Section: Anion-conducting Membranes: Psu-qa and Sa-peekmentioning
confidence: 75%
“…PSU results more permeable to hydrogen (788.4 vs 108.6 cm 2 min -1 ) 25,26 and oxygen (82.8 vs 6.6 cm 2 min -1 ) 25, 27 gas.…”
Section: Introductionmentioning
confidence: 94%